Development of an integrated, evidence-based management model for chronic non-communicable diseases and their risk factors, in a rural area of Limpopo Province, South Africa - Maimela, Eric (University of Limpopo, 2016)
Background: Chronic disease management (CDM) is an approach to health care that keeps people as healthy as possible through the prevention, early detection and management of chronic diseases. This approach offers holistic and comprehensive care, with a focus on rehabilitation, to achieve the highest level of independence possible for individuals.The aim of this study was to develop an integrated, evidence-based model for the management of chronic non-communicable diseases in a rural community of the Limpopo Province, South Africa. Methods: The study was conducted at Dikgale Health and Demographic Surveillance System (HDSS) site is situated in Capricorn District of Limpopo Province in South Africa. This study followed mixed methods methodology with an aim on integrating quantitative and qualitative data collection and analysis in a single study to develop an intervention program in a form of model to improve management of chronic diseases in a rural area. Therefore, this included literature review and WHO STEPwise approach to surveillance of NCD risk factors for quantitative techniques and focus group discussions, semi-structures interviews and quality circles for qualitative techniques. In the surveillance of NCD risk factors standardised international protocols were used to assess behavioural risk factors (smoking, alcohol consumption, fruit and vegetable consumption, physical activity) and physical characteristics (weight, height, waist and hip circumferences, and blood pressure). A purposive sampling method was used for qualitative research to determine knowledge, experience and barriers to chronic disease management in respect of patients, nurses, community health workers (CHWs), traditional health practitioners (THPs) and managers of chronic disease programmes. Data were analysed using STATA 12 for Windows, INVIVO and Excel Spreadsheets. Results: The study revealed that epidemiological transition is occurring in Dikgale HDSS. This rural area already demonstrates a high burden of risk factors for non-communicable diseases, especially smoking, alcohol consumption, low fruit and vegetable intake, physical inactivity, overweight and obesity, hypertension and dyslipidaemia, which can lead to cardiovascular diseases. The barriers mostly mentioned by the nurses, patients with chronic disease, CHWs and THPs include lack of knowledge of NCDs, shortages of medication and shortages of nurses in the clinics which cause patients to stay for long periods of time in a clinic. Lack of training on the management of chronic diseases, supervision by the district and provincial health managers, together with poor dissemination of guidelines, were contributing factors to lack of knowledge of NCDs management among nurses and CHWs. THPs revealed that cultural insensitivity on the part of nurses (disrespect) makes them unwilling to collaborate with the nurses in health service delivery. x The model developed in this study which was the main aim of the study describes four interacting system components which are health care providers, health care system, community partners and patients with their families. The main feature of this model is the integration of services from nurses, CHWs and THPs including a well-established clinical information system for health care providers to have better informed patient care. The developed model also has an intervention such as establishment of community ambassadors. Conclusion: Substantially high levels of the various risk factors for NCDs among adults in the Dikgale HDSS suggest an urgent need for adopting healthy life style modifications and the development of an integrated chronic care model. This highlights the need for health interventions that are aimed at controling risk factors at the population level in order to slow the progress of the coming non-communicable disease epidemic. Our study highlights the need for health interventions that aim to control risk factors at the population level, the need for availability of NCD-trained nurses, functional equipment and medication and a need to improve the link with traditional healers and integrate their services in order to facilitate early detection and management of chronic diseases in the community. The developed model will serve as a contribution to the improvement of NCD management in rural areas. Lastly, concerted action is needed to strengthen the delivery of essential health services in a health care system based on this model which will be tasked to organize health care in the rural area to improve management and prevention of chronic illnesses. Support systems in a form of supervisory visits to clinics, provision of medical equipments and training of health care providers should be provided. Contribution from community partners in a form of better leadership to mobilise and coordinate resources for chronic care is emphasized in the model. This productive interaction will be supported by the district and provincial Health Departments through re-organization of health services to give traditional leaders a role to take part in leadership to improve community participation.
Thesis(Ph.D.(Medical Science)) -- University of Limpopo, 2016
Keywords: Non-communicable diseases; Chronic disease management; Chronic diseases; Evidence-based medicine